Pengaruh Profitabilitas, Likuiditas, dan Struktur Aset Terhadap Kebijakan Hutang Pada Perusahaan Sektor Industrial - Putra, Charli; Muhammad, Maulana Malik (STREAMING, 2024)
The strategy in determining a company’s debt policy must be considered wisely to avoid the risk of bankruptcy in the future. The purpose of this research is to determine the influence of profitability, liquidity, and asset structure on company debt policy. This research use quantitative methods with purposive sampling criteria as the basis for selecting data samples. The data collection method in this research uses observation of published financial report. The number of samples in this research was 66 sample obtained from 16 industrial sector companies listed on the Indonesia Stock Exchange. Later, the data will be processed with IBM SPSS Statistics 23 software as a useful program to assist writers in processing various data. The result of this research show that profitability has a negative and significant influence on debt policy, liquidity also has a negative and significant influence on debt policy, while asset structure apparently does not have a significant influence on debt policy.